Serodiscordance in chronic Chagas disease diagnosis: a real problem in non-endemic countries. (September 2016) - Moure, Z.; Angheben, A.; Molina, I.; Gobbi, F.; Espasa, M.; Anselmi, M.; Salvador, F.; Tais, S.; Sánchez-Montalvá, A.; Pumarola, T.; Albajar-Viñas, P.; Sulleiro, E.
Abstract: According to the WHO, chronic Chagas disease (CD) diagnosis is based on two serological techniques. To establish a definitive diagnosis, the results must be concordant. In cases of discordances, the WHO proposes repeating serology in a new sample, and if results remain inconclusive, a confirmatory test should be performed. This study, conducted at two Tropical Medicine Units in Europe over 4 years, aims to assess the diagnostic yield of TESA- (trypomastigote excreted–secreted antigens) blot as a confirmatory technique in patients with inconclusive and discordant results. Of 4939 individuals screened, 1124 (22.7%) obtained positive results and 165 (3.3%) discordant results. Serology was repeated in 88/165 sera and discrepancies were solved in 25/88 (28.4%) cases. Patients without a definitive diagnosis were classified in two different groups: Group 1, including patients with inconclusive results despite retesting ( n = 63), and Group 2, including patients with discordant results not retested ( n = 77). TESA-blot was performed for all of Group 1 and 39/77 of Group 2 and was positive for 33/63 (52.4%) and 21/39 (53.8%), respectively. Analysis of Group 1 results showed a moderate agreement between results of the ELISA based on native antigen and TESA-blot (κ 0.53). In contrast, a clear disagreement was observed between the ELISA based on recombinant antigens and TESA-blot (κ <0). A sizeable proportion of patients are suspected to have CD with inconclusive results or in whom re-testing is not feasible. TESA-blot was positive in half of these patients, highlighting the need for a confirmatory assay in European centres caring for exposed individuals.